In vivo validation of highly customized cranial Ti-6AL-4V ELI prostheses fabricated through incremental forming and superplastic forming: an ovine model study - Silvia Brogini; Alberto Crovace; Antonio Piccininni; Giuseppe Serratore; Gregorio Marchiori; Melania Maglio; Pasquale Guglielmi; Angela Cusanno; Luigi De Napoli; Romina Conte; Milena Fini; Giuseppina Ambrogio; et al. (Scientific Reports, 2024)
Abstract Cranial reconstructions are essential for restoring both function and aesthetics in patients with craniofacial deformities or traumatic injuries. Titanium prostheses have gained popularity due to their biocompatibility, strength, and corrosion resistance. The use of Superplastic Forming (SPF) and Single Point Incremental Forming (SPIF) techniques to create titanium prostheses, specifically designed for cranial reconstructions was investigated in an ovine model through microtomographic and histomorphometric analyses. The results obtained from the explanted specimens revealed significant variations in bone volume, trabecular thickness, spacing, and number across different regions of interest (VOIs or ROIs). Those regions next to the center of the cranial defect exhibited the most immature bone, characterized by higher porosity, decreased trabecular thickness, and wider trabecular spacing. Dynamic histomorphometry demonstrated differences in the mineralizing surface to bone surface ratio (MS/BS) and mineral apposition rate (MAR) depending on the timing of fluorochrome administration. A layer of connective tissue separated the prosthesis and the bone tissue. Overall, the study provided validation for the use of cranial prostheses made using SPF and SPIF techniques, offering insights into the processes of bone formation and remodeling in the implanted ovine model.